Un panorama des propositions économiques en matière de soutenabilité - Franck-Dominique Vivien (VertigO)
The objective of sustainable development is translated in very different ways. We propose a panorama of economic proposals related to sustainability. This one is setting on three groups of theoretical works: the first one, which is the point of view of mainstream in economics, brings forward the idea of sustainable growth as a necessary and sufficient condition to have a sustainable development; the second, more conscious of physical limits, try to elaborate socio-environmental constraints, inside of which economic development must go on; the third one, influenced by third world experiences, insists on social inequalities and question the sense of the notion of development.